Prevention of Stunting with the Edu-1000 Application in Pregnant and Breastfeeding Women in Kupang District - Bringiwatty Batbual; Wanti; Demsa Simbolon; Fransiskus Salesius Onggang; Melinda Rosita Wariyaka; Oklan B. T. Liunokas; Sabinus Bungaama Kedang (Postgraduate, University of Mataram, 2024)
The prevalence of stunting has decreased compared to the previous 2 years. However, this reduction still does not meet WHO's target, namely the prevalence of stunting <20%, while the prevalence of stunting in Indonesia in 15 provinces is still above 20%. The aim of this research is to analyze stunting prevention with the edu-1000 first day of birth application in pregnant women and breastfeeding mothers in Kupang district. method. The research design used in this research is